Law no. 82/2002 on the protection of the Intellectual property rights = قانون حماية حقوق الملكية الفكرية - Egypt. (2025)
Law no. 82/2002 on the protection of the intellectual property rights – book 1: patents foe invention and utility designs, integrated circuits layout charts, and non-expounded information – book 2: trade marks and data, the geographical indices and the industrial drawings and designs – book 3: author’s rights and proximal rights -- book 4: botanical items